Tackling issues and initiating public debate: New Zealand Association of Scientists 1974–91 - Gregory, Geoff (New Zealand Science Review, 2014)
This is part 3 of the history of New Zealand Association of Scientists. Parts 1 and 2 were in New Zealand Science Review (2013) vol. 70(1): 10–19; and 70(4): 65–76.